Gold nanoparticles (AuNPs) impair LPS-driven immune responses by promoting a tolerogenic-like dendritic cell phenotype with altered endosomal structures. Issue 16 (15th April 2021) - Michelini, Sara; Barbero, Francesco; Prinelli, Alessandra; Steiner, Philip; Weiss, Richard; Verwanger, Thomas; Andosch, Ancuela; Lütz-Meindl, Ursula; Puntes, Victor F.; Drobne, Damjana; Duschl, Albert; Horejs-Hoeck, Jutta
Abstract : This study shows that gold nanoparticles promote the differentiation of dendritic cells to a tolerogenic-like phenotype, affecting their ability to induce antibacterial immune responses mediated by Th1 cells and to activate central memory T cells. Abstract : Dendritic cells (DCs) shape immune responses by influencing T-cell activation. Thus, they are considered both an interesting model for studying nano-immune interactions and a promising target for nano-based biomedical applications. However, the accentuated ability of nanoparticles (NPs) to interact with biomolecules may have an impact on DC function that poses an unexpected risk of unbalanced immune reactions. Here, we investigated the potential effects of gold nanoparticles (AuNPs) on DC function and the consequences for effector and memory T-cell responses in the presence of the microbial inflammatory stimulus lipopolysaccharide (LPS). Overall, we found that, in the absence of LPS, none of the tested NPs induced a DC response. However, whereas 4-, 8-, and 11 nm AuNPs did not modulate LPS-dependent immune responses, 26 nm AuNPs shifted the phenotype of LPS-activated DCs toward a tolerogenic state, characterized by downregulation of CD86, IL-12 and IL-27, upregulation of ILT3, and induction of class E compartments. Moreover, this DC phenotype was less proficient in promoting Th1 activation and central memory T-cell proliferation. Taken together, these findings support the perception that AuNPs are safe under homeostatic conditions; however, particular care should be taken in patients experiencing a current infection or disorders of the immune system.